Decisional support needed when facing tough decisions: Survey of parents with children having differences of sex development - Gardner, Melissa; Brinkman, William B.; Carley, Meg; Liang, Noi; Lightfoot, Sophie; Pinkelman, Kendra; Speiser, Phyllis W.; Schafer-Kalkhoff, Tara; Suorsa-Johnson, Kristina I.; VanderBrink, Brian; Weidler, Erica M.; Wisniewski, Jessica; et al. (Frontiers in Urology, 2023)
Introduction: Parents of infants and young children newly diagnosed with differences of sex development (DSD) commonly face medical and psychosocial management decisions at a time when they are first learning about the condition and cannot consult their child for input. The aim of this study was to identify areas of greatest need for parental decisional support. Methods: 34 parents of children receiving care for DSD at one of three US children’s hospitals participated in a survey to learn what clinical and psychosocial decisions needed to be made on behalf of their child. Parents were then asked to identify and focus on a “tough” decision and respond to questions assessing factors affecting decision-making, decision-making preferences, decisional conflict, and decision regret. Descriptive analyses were conducted. Results: Decisions about surgery and aspects of sharing information about their child’s condition with others were the two most frequently reported decisions overall, experienced by 97% and 88% of parents, as well as most frequently nominated as tough decisions. Many parents reported mild to moderate levels of decisional conflict (59%) and decision regret (74%). Almost all parents (94%) reported experiencing at least one factor as interfering with decision-making (e.g., “worried too much about choosing the ‘wrong’ option”). Parents universally reported a desire to be involved in decision-making – preferably making the final decision primarily on their own (79%), or together with their child’s healthcare providers (21%). The majority of parents judged healthcare providers (82%) and patient/family organizations (58%) as trustworthy sources of information. Discussion Parents of children with DSD encounter medical, surgical, and psychosocial management decisions. Despite difficulties including emotional distress and informational concerns (including gaps and overload), parents express strong desires to play key roles in decision-making on behalf of their children. Healthcare providers can help identify family-specific needs through observation and inquiry in the clinical context. Together with families, providers should focus on specific clinical management decisions and support parental involvement in making decisions on behalf of young children with DSD.